MiR-543 promotes tumorigenesis and angiogenesis in non-small cell lung cancer via modulating metastasis associated protein 1 - Dawei Wang; Li Cai; Xudong Tian; Wenjun Li (BMC, 2020)
Abstract Objective This study is aimed to explore the role of miR-543 in non-small cell lung cancer (NSCLC), and verify whether miR-543 targets metastasis associated protein 1 (MTA1) to affect tumorigenesis and angiogenesis in NSCLC. Methods Firstly, miR-543 mimic and inhibitor were transfected into A549 cells and H1299 cells. The cells proliferation was tested by MTT and clone formation. The cells apoptosis was analyzed by cytometry. Tube formation assay was used to measure the vascularization of cells. qRT-PCR and Western Blot were used to measure the MTA1 expression. Dual-luciferase assay was used to analyze whether miR-543 targets MTA1. Secondly, MTA1 mimic and inhibitor were transfected into cells to analyze the effect of MTA1 on proliferation and angiogenesis in NSCLC cells. Lastly, the nude mice were used to verify the effect of miR-543 on tumorigenesis and angiogeneisis in NSCLC via modulating MATA1. Results miR-543 overexpression could apparently promote cells proliferation and angiogeneisis in NSCLC cells. Meanwhile, the MTA1 expression was increased after transfecting miR-543 mimic. Dual luciferase reporter assay revealed MTA1 was a downstream target of miR-543. Further studies showed that inhibition of MTA1 weakened the role of miR-543 overexpression in NSCLC cells. Vivo experiments revealed that miR-543 promoted cells proliferation and angiogenesis in tumor tissues via modulating MTA1. Conclusion miR-543 could target MTA1 to promote tumorigenesis and angiogenesis in NSCLC via targeting MTA1.